Alternative protein based on Eisenia foetida in the nutrition of native chickens - Huauya Pablo, Percy Segundo (2025)
The growing demand for alternative protein sources in animal feed has increased interest in earthworm meal (EM) as a sustainable input in poultry production. This study evaluated the effect of its inclusion in the diet of native chickens on productive and economic parameters. Four treatments were applied with inclusion levels ranging from 0 to 12 % EM, recording cumulative feed intake, body weight, weight gain, feed conversion ratio, mortality, and profitability over a 25-day period. In addition, the nutritional composition of EM was determined through proximate analysis. The results showed significant differences (p < 0.05) in body weight, with a progressive increase from 355.51 g to 427.86 g. Feed conversion improved from 2.40 to 2.08 as the inclusion level increased, while feed intake showed an upward trend without statistical differences. No mortality was recorded and feathering was uniform. The 12% EM treatment presented the best productive performance. Regarding the composition of the meal, protein content was 57.46 %, fat 5.33 %, ash 16.11 %, and fiber 0.55 %. These findings suggest that EM sustainably improves performance in native chickens.